2002
DOI: 10.1038/sj.cgt.7700497
|View full text |Cite
|
Sign up to set email alerts
|

Electrotransfer of gene encoding endostatin into normal and neoplastic mouse tissues: Inhibition of primary tumor growth and metastatic spread

Abstract: Electroporation -mediated gene transfer relies upon direct delivery of plasmids into cells permeabilized by electric fields, a method more efficient than transfer using nonviral vectors, although neither approaches the transfer efficiency of viral vectors. Here we studied electrotransfer of a gene encoding an angiogenesis inhibitor ( endostatin ) into primary tumors and muscle tissues, which would serve as a site of synthesis and secretion into the bloodstream of a therapeutic antimetastatic protein with syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
23
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…In our experiments, low-voltage in vivo electroporation was applied, but to achieve the same quantity of heat, longer loading periods can be employed. Cichon et al 22 reported that the electrotransfer of the gene encoding endostatin into neoplastic mouse tissue resulted in the inhibition of primary tumor growth and metastatic spread. They reported that there was no improvement in the efficiency of gene transfers into tumors beyond a threshold voltage, and that distinct tissue damage could be seen at higher voltages, especially with combinations of high voltage and lengthy impulse time.…”
Section: Low-voltage Ep and Antiangiogenic Gene Therapy M Uesato Et Almentioning
confidence: 99%
“…In our experiments, low-voltage in vivo electroporation was applied, but to achieve the same quantity of heat, longer loading periods can be employed. Cichon et al 22 reported that the electrotransfer of the gene encoding endostatin into neoplastic mouse tissue resulted in the inhibition of primary tumor growth and metastatic spread. They reported that there was no improvement in the efficiency of gene transfers into tumors beyond a threshold voltage, and that distinct tissue damage could be seen at higher voltages, especially with combinations of high voltage and lengthy impulse time.…”
Section: Low-voltage Ep and Antiangiogenic Gene Therapy M Uesato Et Almentioning
confidence: 99%
“…In hindsight, it would be preferable to deliver the angiogenic factors prior to surgical removal of a tumor in order to ensure that serum levels of angiostatin and endostatin have reached a maximum level. Our approach using naked plasmids could potentially be enhanced by electrotransfer of angiostatin and endostatin plasmids into muscle tissues as exemplified by Cichon et al 9 Antiangiogenic therapy is widely regarded as a promising treatment strategy to combat cancer based on the fact that most tumors are dependent on angiogenesis for survival. However, despite many successful animal experiments employing antiangiogenic therapies, disappointing reports have emerged recently, particular when antiangiogenic therapies have been applied to human beings.…”
Section: Discussionmentioning
confidence: 99%
“…They both inhibit endothelial cell migration and proliferation, and induce the regression of a wide variety of established tumors of mouse, rat and human origin, including metastases. [4][5][6][7][8][9] The tumor-suppressor activity of angiostatin may arise from its ability to inhibit the proliferation of endothelial cells by binding to the a/bsubunits of ATP synthase, 10 inducing apoptotic cell death, 5 by subverting adhesion plaque formation and thereby inhibiting the migration and tube formation of endothelial cells, and/or by downregulating vascular endothelial growth factor (VEGF) expression. 11,12 The latter feature of angiostatin is not retained in all tumor models, as it had no effect on VEGF expression in two reports, 13,14 and even slightly upregulated VEGF expression in EL-4 tumors.…”
mentioning
confidence: 99%
“…Several other studies have employed in vivo electroporation (direct electroporation of solid tumors) with some successes. For example, Cichon et al 23 used in vivo electroporation to administer the ES transgene into normal and neoplastic mouse tissues to treat RENCA as well as B16F10 melanoma. In that study, ES could similarly control primary and metastatic tumor development.…”
Section: Discussionmentioning
confidence: 99%